2014
DOI: 10.1111/aos.12327
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of intraocular pressure and associated systemic factors in a Korean population: The Korea National Health and Nutrition Examination Survey

Abstract: ABSTRACT.Purpose: To investigate the distribution of intraocular pressure (IOP) and its associated factors in a large Korean population based on the data from the nationwide cross-sectional survey. Methods: We obtained 2009-2010 data from the Korea National Health and Nutrition Examination Survey (KNHANES) (n = 17 901). After excluding individuals under 19 years of age, a total of 13 431 subjects were enrolled. All participants completed a comprehensive questionnaire and underwent an ocular examination includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 31 publications
5
39
1
2
Order By: Relevance
“…However, we found no significant association between age and IOP, in accordance with another Korean population based study by Kim et al [10]. The possible reason for the inconsistent results between studies is that the inclusion criteria and the adjusting factors are different between studies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, we found no significant association between age and IOP, in accordance with another Korean population based study by Kim et al [10]. The possible reason for the inconsistent results between studies is that the inclusion criteria and the adjusting factors are different between studies.…”
Section: Discussionsupporting
confidence: 86%
“…Regarding refractive error, a negative association with IOP has been reported in several studies [10], [15], [16]. Myopia has emerged as a major health issue worldwide, and its prevalence has increased rapidly in the past few decades, particularly in East Asia [17][21].…”
Section: Introductionmentioning
confidence: 94%
“…When we applied the same criteria as that of the former study, our patients showed a lower rate of myopia (46 %) and a higher rate of hyperopia (41 %) compared to the study by Yoon et al Bollinger et al [18] suggested that the high prevalence of hyperopia might be related to low IOP, although the authors failed to show a relationship between the degree of hypotony and hyperopia. The mean IOP among our patients (8.74 ± 3.54 mmHg) was also lower than that of the general Korean population (13.99 ± 2.75 mmHg) [21].…”
Section: Discussioncontrasting
confidence: 68%
“…15,25 In this study, univariate regression showed a negative correlation between HDL-C and IOP but a positive correlation between LDL-C and IOP, which are consistent with the findings of a recent study. 26 Even though multivariate regression analysis adjusted for age, BMI, SBP, and DBP showed a negative correlation between HDL-C and IOP, a positive correlation between LDL-C and IOP, previous studies differ markedly regarding the natures of the correlations between IOP and HDL-C or LDL-C, and thus, additional studies are needed to clarify the situation.…”
Section: Discussionmentioning
confidence: 96%